Understanding Christian translation and its missiological relevance - Akinyemi O. Alawode (HTS Teologiese Studies/Theological Studies, 2024)
Christian translation is integral to Christian missions that benefit the ingenious people and the gospel. Among early missionary activities, translations of the Bible to vernacular language have tremendous implications for the gospel propagation. Its roots are well spelt out in the early church, which endorsed Christianity as a universal faith. The researchers observe the historical and missiological perspective of Bible translation. They used library materials and internet sources to explain the meaning of translation, such as explaining a text language in the context of the recipients. This article contains a biblical basis for Bible translations, as it was from the early scriptures, and it concludes by explaining the relevance of Christian translation in terms of literacy, preservation of culture and freedom from slavery, among others. Christian translation has helped to create different versions of the Bible; the New Testament alone is available in 1551 languages out of over 7100 languages worldwide. Christian translation shows that Christian missionaries are not another form of a colonising agency because their activities resulted in actions that led to the end of colonisation in many parts of Africa. The author used a descriptive research method for this article.